Multi scale modelling of the hygro-mechanical behavior of Rhecktophyllum camerunense vegatable fibers - Noutegomo Boris; Betene Ebanda Fabien; Atangana Ateba (Results in Materials)
The study of Rhecktophyllum Camerunense (RC) fibers as reinforcement of polymer matrix began in 2008 and has already demonstrated their ability to replace the glass fibers. In this paper, the influence of humidity on the mechanical behavior of plant fiber is studied and a multiscale model is proposed. The moisture absorption of RC fibers is studied through a multi concentric cylinder model developed based on the work of Marklund. Using mechanical properties of the three main components of natural fibers; cellulose, hemicelluloses and lignines, the mechanical properties and hygroscopic coefficients of layers S1, S2 and S3 of RC fiber are calculated following the relative humidities of 23 %, 54 % and 75 %. The results lead to the conclusion that there is an influence of relative humidity on the mechanical properties whether at the microscopic level of constituents or the mesoscopic scale of layers and the macroscopic scale of RC fiber structure. That influence is negative because it drops the mechanical properties of the fiber. This work permitted to validate the experimental study done on the RC fiber for the same relative humidities.